Hospital epidemiologists' and infection preventionists' opinions regarding hospital-onset bacteremia and fungemia as a potential healthcare-associated infection metric. (1st April 2019) - Dantes, Raymund B.; Abbo, Lilian M.; Anderson, Deverick; Hall, Lisa; Han, Jennifer H.; Harris, Anthony D.; Leekha, Surbhi; Milstone, Aaron M.; Morgan, Daniel J.; Safdar, Nasia; Schweizer, Marin L.; Sengupta, Sharmila; et al.
Abstract: Objective: To ascertain opinions regarding etiology and preventability of hospital-onset bacteremia and fungemia (HOB) and perspectives on HOB as a potential outcome measure reflecting quality of infection prevention and hospital care. Design: Cross-sectional survey. Participants: Hospital epidemiologists and infection preventionist members of the Society for Healthcare Epidemiology of America (SHEA) Research Network. Methods: A web-based, multiple-choice survey was administered via the SHEA Research Network to 133 hospitals. Results: A total of 89 surveys were completed (67% response rate). Overall, 60% of respondents defined HOB as a positive blood culture on or after hospital day 3. Central line-associated bloodstream infections and intra-abdominal infections were perceived as the most frequent etiologies. Moreover, 61% thought that most HOB events are preventable, and 54% viewed HOB as a measure reflecting a hospital's quality of care. Also, 29% of respondents' hospitals already collect HOB data for internal purposes. Given a choice to publicly report central-line–associated bloodstream infections (CLABSIs) and/or HOB, 57% favored reporting either HOB alone (22%) or in addition to CLABSI (35%) and 34% favored CLABSI alone. Conclusions: Among the majority of SHEA Research Network respondents, HOB is perceived as preventable, reflective of quality of care, and potentially acceptable as a publicly reported quality metric. Further studies on HOB are needed, including validation as a quality measure, assessment of risk adjustment, and formation of evidence-based bundles and toolkits to facilitate measurement and improvement of HOB rates.